Computational fluid dynamics analysis of the effect of throat diameter on the fluid flow and performance of ejector. Issue 3 (15th July 2020) - Salehi, Mohammadreza; Pourmahmoud, Nader; Hassanzadeh, Amir; Hoseinzadeh, S.; Heyns, P.S.
Abstract : Purpose: Using the computational fluid dynamics (CFD) technique, this paper aims to investigate the influence of key parameters such as throat diameter; the suction ratio on the flow field behaviors such as Mach number; pressure; and temperature. Design/methodology/approach: To investigate the effect of throat diameter, it is simulated for 4, 6, 8 and 10 mm as throat diameters. The governing equations have been solved by standard code of Fluent Software together with a compressible 2 D symmetric and turbulence model with the standard k–ε model. First, the influence of the throat diameter is investigated by keeping the inlet mass flow constant. Findings: The results show that a place of shock wave creation is changed by changing the throat diameter. The obtained results illustrate that the maximum amount of Mach number is dependent on the throat diameter. It is obtained from the results that for smaller throats higher Mach numbers can be obtained. Therefore, for mixing purposes smaller throats and for exhausting bigger throats seems to be appropriate. Originality/value: The obtained numerical results are compared to the existing experimental ones which show good agreement.